Pengaruh Leverage, Liquidity, Ukuran Perusahaan, Nilai Tukar, dan Profitability Terhadap Keputusan Lindung Nilai (Hedging) - Salwa Nurul Hilaliah; Hermanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to examine the influence of leverage, liquidity, company size, exchange rates, and profitability on hedging decisions. This study uses the population of companies that are consistently listed on the Indonesia Stock Exchange during the period 2018 to 2023, the information in this study comes from the annual report.  consistently listed on the Indonesia Stock Exchange during the period 2018 to 2023, the information in this study comes from the Annual Report. Purposive sampling is employed in this study, utilizing secondary data with a total of 144 data points from 40 companies continuously listed on the Indonesia Stock Exchange during the period of 2018 to 2023. The study measures variables including hedging decisions, leverage (debt to equity ratio), liquidity (current ratio), company size (total assets), exchange rates (mid-rate), and profitability (return on assets). Logistic regression analysis is conducted using SPSS data processing software. The study finds that leverage positively and significantly affects hedging decisions, while liquidity, exchange rates, and profitability do not significantly impact hedging decisions. Additionally, company size has a negative and significant influence on hedging decisions.